PENERAPAN OPERANT CONDITIONING DAN REINFORCEMENT TERHADAP HASIL BELAJAR PASSING DALAM PERMAINAN SEPAK BOLA - Suryadi yarso; Mimi Haetami; Fitriana Puspa Hidasari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThe problem discussed in this study was whether there was the influence of the application of operant conditioning and reinforcement theory on the results of inner leg passing learning in the learning game of soccer in SMP 10 Pontianak. The purpose of this study was to determine the effect of the application of operant conditioning and reinforcement theory on the results of inner leg passing learning in soccer game learning at 10 Pontianak Junior High School. The research was carried out by descriptive qualitative method involving two variables, namely the independent variable operant conditioning and reinforcement theory and the dependent variable which was the result of inner foot passing learning in the learning of soccer games. The subjects in this study were students of class VII A SMP Negeri 10 Pontianak, totaling 36 students. The results of this study indicate that there is an increase in the results of inner leg passing. The conclusions in this study were that there was an increase in passing of the inner leg in learning soccer games through the application of operant conditioning and reinforcement theory to students of class VIIA Pontianak 10th Middle School Keywords: operant conditioning, reinforcement theory, passing.